KEBIJAKAN HUKUMAN MATI TERHADAP TERPIDANA NARKOTIKA DI INDONESIA DITINJAU DARI HAK ASASI MANUSIA - Syawal Amry Siregar; Ade Yuliany Siahaan; Marnaek Tua Kevin Purba (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
Indonesia is one of the countries that still imposes a death penalty for certain crimes that fall into the type of extra ordinary crimes. Drugs trafficking crimes is one that falls into the extra ordinary crime types. Over of time, this crime has grown not only from the increasing number of users and dealers but also from the types of drugs themselves so that the Indonesiangovernment requires a strict punishment in overcoming these crimes. On the other hand, the implementation of imprisonment is considered ineffective,in fact, in some cases the convictshave the opportunity to become recidivists and control the crime even more. Therefore, the death penalty policy for drugs convicts is an effort that is expected to eradicate drugs trafficking crimes in Indonesia. The problems wichis studied in this paper is how is the regulation of the death penalty for drugs convicts according to the law in Indonesia, how the effectiveness of the death penalty for drugs convicts and how the death penalty policy for drugs convicts is reviewed by a human rights perspectivity. This research was conducted in a normative juridical manner and is expected to provide a comprehensive explanation of matters relating to the death penalty policy for drugs convicts by a human rights perspectivity. Based on the results of this research paper, the death penalty has been regulated in law number 35 of 2009 does not have a deterrent effect on drug offenders. In addition, the death penalty policy for drugs convicts if it viewed from human rights is contradictory because the right to life is the most important right for humans and is contained in the 1945 constitution as the written basic law for the Indonesian nations.